Lessons Learned from Challenges in Developing a Test Setup to Replace a Faulty Universal Testing Machine - Ling, Jen Hua; Chin, Wei Jun; Ling, Bing Liang; Su, Vincent Liang Cheng (Indonesian Journal of Computing, Engineering, and Design (IJoCED), 2025)
This study addresses the challenges encountered in developing a test setup to replace a malfunctioning Universal Testing Machine (UTM). The setup was designed using a portal frame, hydraulic jack system, data acquisition system, and beam reaction system to simulate compressive forces on concrete-filled tube (CFT) specimens. Significant issues arose, including deformation of the steel plate, which failed to uniformly distribute stress; excessive out-of-plane deformation of the supporting steel beam; and load cell damage due to overloading. These problems resulted from inappropriate load simulation, inaccurate measurements, and safety concerns. Despite multiple mitigation attempts, the setup was ultimately unsuccessful and discontinued. Displacement discrepancies reached 90.9% and 76.7% in Setup 1 and Setup 2, respectively, while strength discrepancies of 31.9% to 46.2% were observed in identical specimens. This research highlights the complexities of replicating precise testing conditions and underscores the need for thorough planning and expertise in experimental design. To guide future setups, this study recommends a strength hierarchy, in ascending order: specimen, hydraulic cylinder, load cell, steel beam, and portal frame, to ensure safety and reliability in test execution.